Inhibition Zone of Soapnuts Extract (Sapindus rarak) Agains Candida Albicans - Kurniawan, Salsabila Yunita; Novitarini, Novitarini (Jurnal Pijar Mipa, 2025)
Candida albicans infection is a common health problem in Indonesia and other tropical countries. Synthetic antifungals have been shown to develop resistance against Candida albicans. Therefore, it is necessary to explore potential natural ingredients as alternatives to synthetic antifungals. Soapnut fruit contains secondary metabolites that can inhibit or kill Candida albicans. The purpose of this study was to test the antifungal activity of Soapnuts fruit by examining the inhibition zone. The inhibition zone was tested using the well diffusion method. In this study, Soapnuts extract was used with concentrations of 25%, 50%, 75%, and 100%. The results showed a probability value (p) of 0.008 < 0.05, indicating a significant difference between each concentration of soapnut extract and the inhibition zone diameter of Candida albicans. The best results were shown by the 100% concentration, which produced an average inhibition zone of 27.50 mm, categorized as very strong inhibition. Soapnut fruit extract exhibits a potent inhibitory effect against Candida albicans. This study can serve as a reference in the development of antifungal agents from Soapnuts fruit extract.